Molecular diversity and functional prediction of Foliar endophytic bacteria in Tectona grandis (Teak) estimated by 16S rDNA sequence analysis - Patturaj, Maheswari; Kannan, Nithishkumar; Warrier, Rekha R.; Jacob, John Prashanth; Yasodha, Ramasamy (Vol. 150, No. 6B (December 2021) pages 1677-1687.)
The multi-layer structure of leaves supports endophyte colonization facilitating compatible plant-microbe interactions. Endophytic microbiota, including bacteria, influence the vital activities of plants. Yet, information on bacterial communities in leaves of forest trees largely remains unknown. -Title page.